The investigation of Kulula (Slow XS) Lounges for the South African Low-Cost Carrier - Muchena, Nyasha Lynnete (My University, 2017)
Purpose: This consultancy report is aimed at providing empirical evidence for consumer intent to purchase and preference for a SLOW XS lounge at the Lanseria International Airport as well as an evaluation of Comair’s organizational readiness to support its establishment. Methodology: The methodology consisted of a quantitative section which was done via a conjoint survey of the Kulula passengers and distributed online. Scenarios with different levels of defined attributes were presented as options for the passengers after which a conjoint analysis was done in the Sawtooth software before interpreting the results. The consultancy report also included a qualitative component where internal Comair staff were interviewed via face-to-face interviews and content analysis was done to determine the organization’s readiness to establish a Kulula lounge at the Lanseria International Airport. Results: This consultancy report outcomes showed that brand and price have greater importance to consumers when compared to ambiance and food and beverage quality. In assessing consumer purchase intent and preference for an airline lounge, the market indicated sensitivity to price, however, the brand attribute is influential enough to convince some passengers to purchase a lounge service for a high valued brand at a higher price. The SLOW XS brand is perceived to be of high value in the airport environment hence the launch at the Lanseria international airport is likely to succeed much like its predecessor SLOW lounge brand. Limitations: The results of this study cannot guarantee the actual purchase behavior due to the fact that the movement of the purchase share is only indicative and not definite. The time set for the data collection did not allow for a big enough sample to draw meaningful conclusions. Conclusion: Although market share is sensitive to price, there are consumers that are willing to pay for a quality service such as an airport lounge to enhance their travel experience. This is consistent with the demand by consumers for quality services as highlighted in the literature. Recommendations: Comair is able to launch a new SLOW XS brand due to its brand power in the airport environment. It also does not need to drop its value of R250 since it can still make more revenue from passengers willing to pay that that price, than if it lowers the price to R100 where it would sell more lounge passes but make less revenue. However, the sample size used in the conjoint survey was not big enough to draw meaningful conclusions and therefore the study should be repeated with a sample of at least 1000 participants. Further studies can also include demographic profiles in the market simulation to identify the exact market segment of passengers who are willing to purchase SLOW XS lounge access.
MBA
Keywords: Airport terminals -- South Africa. Airport buildings.